Factors that influencing the fluctuation price of rubber in the market / Wan Nor Syamimi Wan Jusoh - Wan Jusoh, Wan Nor Syamimi (2010)
The development of Malaysia’s primary commodities sector has had a major impact on the country’s economic achievements in the last few decades. The Malaysian natural rubber (NR) industry has had over 100 years of existence. It has grown to become an important industry in Malaysia, especially in terms of employment opportunities for rural smallholders' families, foreign exchange earnings and downstream activities. However, over the last few years the NR industry has faced a multitude of problems in the fields of economics, production and related aspects. This study had been done to identify the factors that will influence the fluctuation price of rubber in the market and also the action taken to solve this problem. For the completion of this study, secondary data had been use as a data collection. The data is given by the company and also from external resources such as journals, reference book and internet. In this study, it had covered the aspect that can influence the fluctuation price of rubber in the market and the way to handle this problem. By comparing between Malaysia and other countries practice, we can know which the best way to fix the problem that they had faced.